The Fault in our Stars – Starry-coloured Halos in Occipital Lobe Infarct - Kaaviya Asokan; Venipriya P. Sigamani; Renuka Srinivasan (TNOA Journal of Ophthalmic Science and Research)
Coloured halos occur due to the accumulation of fluid in the corneal epithelium and due to alterations in the refractive condition of the corneal lamellae. They are usually seen in glaucoma, cataract, and sometimes in conjunctivitis as well. Visual hallucination are observed in migraines, seizure disorders, and sometimes psychiatric disorders. This presentation is about a 55-year-old female who came to casualty with complaints of a severe headache and sudden onset of defective vision in the right side for 3 days. She also complained of seeing multi-coloured rings in a star pattern, each episode lasting for 10 to 15 min. A confrontation test was performed, which showed right homonymous hemianopia. A CT scan of the Brain was conducted, revealing a left subacute occipital lobe infarct. Gonioscopy and dilated fundus examination showed no evidence of glaucoma. In summary, coloured halos occur not only due to glaucoma or cataract, but they can also, though rarely, suggest occipital lobe infarcts. A thorough history and a detailed systemic and ocular examination in all cases of coloured halos will help in diagnosing rare causes.